Medical nutritional therapy on schizophrenic patient with grade 2 obesity and continued antipsychotic drug use - Andry Kelvianto; Wiji Lestari; Diana Sunardi (Indonesian Nutrition Association, 2022)
Patients suffering from schizophrenia have an elevated risk for obesity and metabolic syndrome due to multiple factors, including antipsychotic drug consumption. Diet and lifestyle modification remained the firstline modalities for management of obesity in patients with schizophrenia. Metformin has been recommended for preventing weight gain, including for schizophrenic patients with long-term consumption of psychiatric medication.